Flash sintering of lead free perovskite oxides towards sustainable processing of materials for energy and related applications - Serrazina, Ricardo Nazaré (2021)
Piezoelectrics as K0.5Na0.5NbO3 (KNN) have currently an emerging importance due to their lead-free nature and high transition temperature, which permits a wide range of high-tech applications as sensors, actuators, energy harvesters, biosensors, etc. However, monophasic dense KNN products are yet difficult to obtain, due to the high temperature and long time of conventional sintering processes. This PhD proposes a new method to densify materials abruptly above a threshold condition using FLASH sintering, where the densification occurs by a combination of furnace environment (temperature and/or atmosphere) and electrical field directly applied to the specimen. There are several proposed mechanisms for FLASH. Joule heating is the most reported one, but also defectrelated theories have been proposed. The phenomena are not yet completely understood, but most probably, FLASH sintering is a combination of both effects, with particle surfaces energy and conductivity performing a significant role. The present work aims to exploit FLASH for sintering of KNN ceramics but also to depict the fundamental phenomena behind FLASH sintering, and specifically, FLASH sintering of KNN. The ultimate goal is to develop sintering of ceramics towards room temperature, contributing to the energy economy low thermal budget of ceramic industry. The use of Finite Element Modelling (FEM) tools allowed to study the particle orientation effect on the Joule heating during FLASH, while the simulated temperature gradients were used to explain the presence of FLASH sinteringinduced stresses in dense ceramics. The production of different size and purity KNN powders permitted to establish the link between FLASH temperature (TF) and particle size/purity. Following, the establishment of an engineered thermal cycle before the application of the electric field for the FLASH was responsible for increasing the final densification of KNN ceramics to 95%. The link between FLASH parameters, as current density and holding time, was determined and the relationship with final density and grain size of ceramics studied. TEM and FEM studies allowed to propose a FLASH sintering mechanism for KNN, in which the current flow through particles’ surfaces promotes the partial melting of contacts and the particle sliding towards pore removal and compact densification. To allow a significant decrease on the TF of KNN, atmosphere-assisted FLASH sintering (AAFS) was presented, and the temperatures were decreased to TF ≈ 265 ºC, however, the final densification was limited to 79%. The ferroelectric and dielectric performance of FLASH sintered KNN was studied and compared with that of conventionally sintered ceramics. Similar performance was attained after a heat treatment for electrode cure; however, a detailed analysis revealed FLASH sintering-fingerprints in both as-sintered and heattreated ceramics. This work presents a clear contribution for the development of FLASH sintering in ceramics, namely in piezoelectric KNN.